BETWEEN MANAGERIALISM AND THE LEGAL COUNTERCULTURE: THE YALE PROGRAM IN LAW AND MODERNIZATION IN THE HISTORY OF THE GLOBAL 1970S - Giovanopoulou, Afroditi (REI - REVISTA ESTUDOS INSTITUCIONAIS, 2021)
Often described as a period of seismic shifts in world history, the 1970s bear the definitive marks of a conflictual era. Focusing on the unraveling of the postwar liberal consensus, historians of the United States have portrayed this decade as nothing short of an “Age of Fracture,” during which larger narratives about American democracy, the relationship of the individual to the whole, and the relationship between state and society came undone.<a title="" href="https://d.docs.live.net/a4fa3b7694794c6e/REVISTA%20ESTUDOS%20INSTITUCIONAIS/Vol7%20Num2/Artigos%20Internacionais/8.%20Between%20Managerialism%20and%20the%20Legal%20Counterculture%20(Giovanopoulou).docx#_ftn1">[1] International historians point to a dramatic reconfiguration of the international order during the same decade, which saw the completion of a society of nominally equal sovereign states, once aspiring to produce a New International Economic Order but eventually defeated by the 1973 oil crisis and the rise of neoliberalism.<a title="" href="https://d.docs.live.net/a4fa3b7694794c6e/REVISTA%20ESTUDOS%20INSTITUCIONAIS/Vol7%20Num2/Artigos%20Internacionais/8.%20Between%20Managerialism%20and%20the%20Legal%20Counterculture%20(Giovanopoulou).docx#_ftn2">[2] The microcosm of the Yale Program in Law and Modernization illuminates the overlapping themes of protest, disruption, disillusionment and backlash that characterized the 1970s. Established with a significant grant from USAID, the Program, in the years of its operation between 1969 and 1976, was designed as a space of research on America’s legal modernization projects in the global periphery. Soon enough, a diverse cast of characters, united in their interest in the Third World but otherwise quite contrasting in terms of their backgrounds, goals, and aspirations, inhabited this space. Some had direct policy experience working for the American government, while others became interested in the Third World through oppositional politics and a deep suspicion about the possibility of improvement through legal reform. While originally presented as a vessel for designing sound policy-making under the aegis of the USAID and aiding the Third World through managerial socio-legal engineering, the Program unexpectedly transformed into the breeding ground for what would eventually become Critical Legal Studies, and was soon terminated.